(untitled) (International journal of artificial intelligence, 2025)
Blood transfusion is a medical ropcedure in which blood or blood components are transferred from a donor to a recipient. This article discusses the importance of blood transfusion in saving lives, its indications and the necessary precautions to ensure safety. In conclusion, blood transfusion plays a vital role in modern medicine and helps in treating patients with severe blood loss or anemia. This article describes the main purposes and indications of blood transfusion, as well as the procedures used to ensure safety and effectiveness. It also highlights the importance of blood group compatibility, sterilizations and careful donor selection to prevent complications. Furthermore the paper discusses possible risks and emphasizes the need for continuous monitoring during the transfusion process.